2014
DOI: 10.1097/mcg.0b013e3182a8804c
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hypertension and Proteinuria as Markers of Efficacy in Antiangiogenic Therapy for Metastatic Colorectal Cancer

Abstract: To our knowledge, this is the first study to demonstrate the utility of PTN as a surrogate marker of outcome in antiangiogenic therapy for metastatic colorectal cancer. Although HTN is predictive of a significantly higher response rate, the development of PTN during treatment with bevacizumab or tyrosine kinase inhibitor portends poorer survival and should be evaluated prospectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
(24 reference statements)
2
19
1
Order By: Relevance
“…Finally, sorafenib‐induced hypertension predicted a better outcome of cancer patients. This should not come as a surprise, as numerous reports (only few cited here) have shown a similar finding in antiangiogenic cancer therapy . As a matter of fact, when different VPIs were compared head‐to‐head, the ones with more frequent hypertension also had longer progression‐free survival .…”
supporting
confidence: 76%
“…Finally, sorafenib‐induced hypertension predicted a better outcome of cancer patients. This should not come as a surprise, as numerous reports (only few cited here) have shown a similar finding in antiangiogenic cancer therapy . As a matter of fact, when different VPIs were compared head‐to‐head, the ones with more frequent hypertension also had longer progression‐free survival .…”
supporting
confidence: 76%
“…Our study shows a strong correlation between the development of hypertension and treatment efficacy, with a 2.7‐fold reduction in the risk of progression. This development of an anti‐VEGF class toxicity as an efficacy marker has been reported with other anti‐angiogenic drugs . Retrospective studies have reported an association between the development of grade 2/3 hypertension with bevacizumab in first‐line treatment of colon cancer in terms of response rate and PFS .…”
Section: Discussionmentioning
confidence: 63%
“…VEGF pathway). This concept is further supported by evidence that bevacizumab, a monoclonal anti-VEGF-A antibody, and aflibercept, a soluble receptor with affinity to VEGF-A and -B, are also strong inducers of hypertension [20,21]. Inhibition of the VEGF pathway induces hypertension as a class effect; VEGFR-2 is most prominent of those [22][23][24].…”
Section: Pathogenesis Of Hypertension Secondary To Vsp Inhibitionmentioning
confidence: 51%